Effectiveness of a Warm Cinnamon Compress on Pain Intensity in Community-Dwelling Older Adults with Gout Arthritis: A Quasi-Experimental Study - Gani, Abdul; Farama, Dodi Aprika; Pome, Gunardi; Mangunsong, Sonlimar (Chakra Brahmanda Lentera Institute, 2026)
Background: Gout arthritis is a chronic inflammatory joint disorder in older adults that causes persistent pain and limits daily functioning. Despite growing interest in non-pharmacological pain management, most available evidence comes from clinical or hospital-based settings, while evidence from community contexts in LMICs, including Indonesia, remains limited. This study aimed to evaluate the effectiveness of a warm cinnamon powder compress in reducing pain intensity among community-dwelling older adults with gout arthritis. Methods: This quasi-experimental study with a non-equivalent control group pretest–posttest design was conducted in accordance with the TREND reporting guideline at Pagar Agung Health Center, Lahat Regency. A total of 70 older adults with gout arthritis who met the inclusion criteria were recruited and allocated to an intervention group (n = 35) and a control group (n = 35). The independent variable was warm cinnamon powder compress therapy administered once daily for 15 minutes over seven consecutive days, while the dependent variable was pain intensity measured using the Numeric Rating Scale (NRS). The control group received routine care. Data were analyzed using the Wilcoxon signed-rank test for within-group comparisons and the Mann–Whitney U test for between-group differences. Results: The intervention group demonstrated a marked reduction in mean pain scores from 5.11 ± 0.82 at pretest to 2.14 ± 0.93 at posttest, representing a very large within-group effect (Cohen’s d = 3.38), while the control group showed only a minimal change from 5.03 ± 0.79 to 4.89 ± 0.88 (Cohen’s d = 0.17). Between-group comparison indicated a significantly greater reduction in pain in the intervention group than in the control group, with a large effect size (Cohen’s d = 1.54). Clinically, the intervention group predominantly shifted from moderate–severe pain to mild pain categories, indicating a meaningful improvement in pain experience. Conclusion: Warm cinnamon powder compress therapy is effective in reducing pain intensity among older adults with gout arthritis and can serve as a safe and practical complementary intervention in community healthcare settings.